Effects of curcumin and fish oil on motor behavior and biochemical parameters in mice exposed to rotenone - Alves, Barbara da Silva; Cunha, André Brito da; Barros, Paula Alice Bezerra; Monteiro, Linda Karolynne Seregni; Abrão, Lían da Costa; Araújo, Gabriela de Moraes Soares; Miranda, Fernanda Barros de; Ramires Júnior, Osmar Vieira; Silva, Dennis Guilherme da Costa; Arbo, Bruno Dutra; Dora, Cristiana Lima; Hort, Mariana Appel (Acta Scientiarum. Biological Sciences, 2024)
Parkinson’s disease is characterized by dopaminergic neuronal loss, mainly in the substantia nigra pars compacta. Currently, pharmacological treatment reduces the symptoms of the disease, however it does not affect its progression, and often leads to significant adverse effects. In this context, natural products have been explored as a potential source of neuroprotective substances. In this study, the neuroprotective potential of curcumin (CUR) and fish oil (FO) was evaluated against rotenone, which serves as a chemically induced experimental PD model. Male Swiss mice were treated with CUR, FO, CUR + FO or vehicle for seven days. On the eighth day, the animals began receiving rotenone in addition to the treatments for 30 days. At the end of the treatment, locomotor function, oxidative stress and toxicological markers were evaluated. Regarding motor parameters, CUR was able to reduce the number of slippages and bradykinesia in animals treated with rotenone. FO also improved motor coordination, but no additional benefits were observed when FO and CUR were associated. Interestingly, FO increased brain lipid peroxidation, which was attenuated when mice were treated with CUR, suggesting a beneficial effect of the association. In conclusion, CUR and FO possess protective properties against rotenone-induced neurotoxicity. However, the potential benefits of their combined use in relation to PD still require further studies. For example, investigating different doses and treatment durations, as well as evaluating parameters that assess neurodegeneration.